Normativity and Historicity of Imam Syafii's Rejection of Hisab in Determining the Beginning of the Hijri Month - Kusdiyana Kusdiyana; Badrun Taman; Mahkamah Mahdi (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This article examines Imam Syafi'i 's thoughts about determining the beginning of the Hijriyah month without using reckoning. The research method used is library research with a socio-political approach. Primary data is taken from the books by Imam Syafi'i and the scholars of the Shafi'i sect. Data were analyzed using interpretation, deductive-inductive, and historical continuity techniques. The findings of this study are that Imam Syafii determines the beginning of the Hijri month by sighting and the testimony of two fair people. If this is not fulfilled, Imam Syafii determines it with stigma, namely the fulfillment of the day in the month with 30 days. The factor of not using reckoning is due to the tendency of Imam Syafii as Nashir al-Hadith, so the meaning of Imam Syafii for